CARBON MONOXIDE INTERACTION WITH PALLADIUM SURFACE: UDC 541.128 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
Activation desorption energy were calculated by Hartree-Fock self-consistent field method in "sbkjc" basis set  for CO on Pd surface. Two different forms (twofold and threefold) of carbon monoxide adsorbs on palladium surface. The calculated data agrees good with experimental data.
Keywords: -